Conceptual design of a hybrid thin layer cascade photobioreactor for microalgal biodiesel synthesis. (23rd July 2020) - Tan, Chung Hong; Tan, Xuefei; Ho, Shih‐Hsin; Lam, Su Shiung; Show, Pau Loke; Nguyen, The Hong Phong
Summary: Even though microalgae are able to produce various valuable metabolites, microalgal culture on an industrial scale still faces challenging difficulties. Open systems may be cheaper to construct, easier to operate and maintain, and possess greater surface area to volume ratio, but they are also easily contaminated, have high water loss due to evaporation, and suffer from unfavorable weather. On the other hand, closed photobioreactor systems possess higher biomass yields, better control over culture parameters, and lower contamination risks. However, photobioreactors are costlier to construct and maintain. Thus, a hybrid semi‐closed thin layer cascade photobioreactor was proposed to cultivate high‐density microalgal cultures for biodiesel production. Computational fluid dynamics analysis was carried out to observe fluid behavior in the hybrid photobioreactor design. The simulation results showed satisfactory performance in the improved design, making the photobioreactor a potential candidate for microalgal biodiesel production.